2020
DOI: 10.5435/jaaos-d-20-00379
|View full text |Cite
|
Sign up to set email alerts
|

Practice Management During the COVID-19 Pandemic

Abstract: On March 14, 2020, the Surgeon General of the United States urged a widespread cessation of all elective surgery across the country. The suddenness of this mandate and the concomitant spread of the COVID-19 virus left many hospital systems, orthopaedic practices, and patients with notable anxiety and confusion as to the near, intermediate, and long-term future of our healthcare system. As with most businesses in the United States during this time, many orthopaedic practices have been emotionally and fiscally d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(130 citation statements)
references
References 4 publications
5
115
0
10
Order By: Relevance
“…Barnett, Mehrotra, and Landon [ 6 ] reported that due to COVID-19, hospitals have laid off employees and reduced salaries, ambulatory practices have considered closing down, and there is a possibility of more closures and bankruptcies. Similarly, orthopedic practices have been forced to limit staff hours, close offices, and reduce salaries during the COVID-19 pandemic greatly affecting allied health professionals within these practices [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Barnett, Mehrotra, and Landon [ 6 ] reported that due to COVID-19, hospitals have laid off employees and reduced salaries, ambulatory practices have considered closing down, and there is a possibility of more closures and bankruptcies. Similarly, orthopedic practices have been forced to limit staff hours, close offices, and reduce salaries during the COVID-19 pandemic greatly affecting allied health professionals within these practices [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of such a crisis provides a timely opportunity for us to re ect and evaluate the use of novel technologies in the workplace. This includes the adoption of telemedicine and telerehabilitation initiatives, allowing patients to be consulted and followed-up in the comfort of their own homes [4,5,[8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Use of CPET in the COVID-19 endemic phase should be a priority, but must be undertaken safely and only when necessary. Indeed clinical resources will remain directed towards tackling the pandemic, 12 and shortages of personal protective equipment demand the correct use and deployment of any investigation (Fig 1).…”
Section: Precautions and Risk Mitigation For Cpet Testingmentioning
confidence: 99%